Social Life, Economic Status and Health Care Delivery Practices of the People of Bede Community of Bangladesh: A Case Study (Stamford Journal of Pharmaceutical Sciences, 2010)
This study was conducted to observe the socio-economical status, living standard and health management practices of the people of the Bede community of Bangladesh. Bedes living in the Savar area of Dhaka district was selected for a case study. To conduct the study, data were obtained through a questionnairebased survey of 700 respondents about their social and economical status, professional practices, standard of living and literacy status, health management and treatment methods used. It has been observed that these mostly nomadic people of the Bede community have a weak socio-economic condition, large family size {(9-16 member family (58.22%); 17-24 member family (22.20%)}, intense smoking habit and a low level of literacy (80.00% people are illiterate). They practice ethno-medicine and snake-charming as their main professional business to earn a living. In offering health care services to people, they use medicaments prepared from various plant and animal parts and minerals and apply various ethno-treatment techniques, like spiritual, physical, mystical and psychological techniques to treat various ailments. Although they practice their age-old traditional system of medicine as their profession to treat others, they have been found to depend largely on Allopathic, Homeopathic and modern Traditional medicines for treating their own illness, particularly when they suffer from  diarrhoea, dysentery, small pox, orthopedic problems, and even snake-bite, which is supposed to be their own specialty. Bedes live below the poverty line.  Key words: Bede community; Social life; Health practices; Economic statusDOI: 10.3329/sjps.v2i2.5823Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 42-47